Growth inhibition of metronidazole-susceptible and metronidazole-resistant strains of Gardnerella vaginalis by Lactobacilli in vitro. - McLean, N W (1996)
Metronidazole resistance was produced in susceptible Gardnerella vaginalis after subculture in the presence of metronidazole. Metronidazole-resistant gardnerellae were less susceptible to growth inhibition by Lactobacillus culture filtrates. A low pH (+/- 4) and lactic acid accounted for 60 to 95% of inhibitory activity, and H2O2 accounted for only 0 to 30%. However, in the presence of myeloperoxidase, H2O2-producing lactobacilli decreased the viability of metronidazole-susceptible gardnerellae 2,000-fold.